Increasing operational efficiency through a combination of workload management, process streamlining, and system enhancement - Aquino, Allen Jude Moises J. (Animo Repository, 2023)
As talent shortages and difficulties in hiring become a common problem for companies globally, the same was true for the bank (Development Bank of the Philippines), especially for our department (Systems Access and Parameter Management Department). With lack of manpower, the department could not fully realize its mandate to support all the bank’s application systems. This lack of manpower combined with the constant pressure to fulfill our mandate subjected us to negative experiences such as burnout and fear, and ultimately formed in us defensiveness and a strong hesitance to accept more work or support additional application systems. This action research is my personal and a collaborative attempt to resolve our department’s issue by reducing such hesitance without relying on additional manpower. Through this action research, we used different tools such as systems thinking and hypothesis testing to gain a deeper understanding of the underlying causes leading to our primary issue while using data to ensure these are valid, existing, and free from our individual or collective biases. With the gained understanding of the issue, we applied relevant tools such as force-field analysis, process maps, and pareto charts, and identified specific interventions in workload management, process streamlining, and system enhancement. Such interventions later proved successful in increasing our department’s operational efficiency and allowed us to accept and support additional application systems. Through our interventions, we successfully reduced the hesitance in our department and are a step closer towards fully realizing our mandate.